B3 Comparison of the effect of a pure CAG repeat and mixed cagcaa repeat on the extent to which the htt gene is aberrantly spliced in knock-in mice. (13th September 2016) - Ali, Nadira S; Osborne, Georgina F; Benjamin, Agnesska C; Sathasivam, Kirupa; Neueder, Andreas; Howland, David; Bates, Gillian P
Abstract : Background: We have previously shown that the HTT gene is incompletely spliced to generated a small exon 1 – intron 1 polyadenylated mRNA that is translated to produce an exon 1 HTT protein. This occurs in all knock-in mouse models of HD, YAC128 mice, BACHD mice and in patient tissues. Through bioinformatics, we predicted that the splicing factor SRSF6 binds to a degenerative motif that includes both the (CAG)n and (CAGCAA)n sequences and have proposed that the ectopic recruitment of SRSF6 is related to this aberrant splicing event. Aims: To compare the effect of (CAG)n and (CAGCAACAGCAACAA)n repeats on the level of expression of the mutant Htt exon1 - intron1 splice product ( Htt exon 1 mRNA). Methods: Knock-in mice were generated that carried either a (CAG)n repeat or a (CAGCAACAGCAACAA)n repeat that encoded matched polyQ tracts of 45, 80 and 105 glutamines. In both cases the genetic manipulation of the Htt locus left a loxP site located approximately 200 bp into intron 1. Results: Colonies of the (CAG)n and (CAGCAACAGCAACAA)n knock-in mice were established on a C57BL/6 background. The levels of the exon 1 Htt mRNA and the full length Htt transcript were measured by quantitative qPCR in the cortex and striatum of heterozygous mice at 2 and 10 months of age. At 2 months of age levels of the exon 1 Htt mRNA were higher in the (CAGCAACAGCAACAA)n mice than in their matched (CAG)n counterparts, and in both cases, the level of this small transcript increased with the length of the repeat. Conclusions: A mixed (CAGCAACAGCAACAA)n repeat promotes the aberrant splicing of mutant Htt to a greater extent than a pure (CAG)n repeat. At 10 months, somatic instability of the (CAG)n but not the (CAGCAACAGCAACAA)n repeat contributes to the comparative levels of this small transcript. Funding: CHDI Foundation